Genomic methylation - Vale, Filipa F. (2015)
The genome sequences of three Helicobacter pylori strains revealed an abundant number of putative restriction and modification (R-M) systems within a small genome (1.60 to 1.67 Mb). Each R-M system includes an endonuclease that cleaves a specific DNA sequence and a DNA methyltransferase that methylates either adenosine or cytosine within the same DNA sequence. These are believed to be a defense mechanism, protecting bacteria from foreign DNA. They have been classified as selfish genetic elements; in some instances it has been shown that they are not easily lost from their host cell. Possibly because of this phenomenon, the H. pylori genome is very rich in R-M systems, with considerable variation in potential recognition sequences. For this reason the protective aspect of the methyltransferase gene has been proposed as a tool for typing H. pylori isolates. We studied the expression of H. pylori methyltransferases by digesting the genomic DNAs of 50 strains with 31 restriction endonucleases. We conclude that methyltransferase diversity is sufficiently high to enable the use of the genomic methylation status as a typing tool. The stability of methyltransferase expression was assessed by comparing the methylation status of genomic DNAs from strains that were isolated either from the same patient at different times or from different stomach locations (antrum and corpus). We found a group of five methyltransferases common to all tested strains. These five may be characteristic of the genetic pool analyzed, and their biological role may be important in the host/bacterium interaction.